Russia and the Rome Statute of the International Criminal Court - A. Y. Skuratova (Московский журнал международного права, 2016)
The present article provides the analysis of the reasons why Russia has changed its position towards the International Criminal Court. The article covers the intermediate results of ICC’s work, including some legal difficulties appeared throughout the proceedings, especially when a state, which is not a party to a Rome statute, can be subject of the Court’s investigation. The present article includes the analysis of report of Prosecutor’s Office, published November 2016, concerning the situation in Ukraine and the Crimea’s referendum. The author considers the legal consequences of the decision of Russian Federation not to be a state-party to the Rome statute of ICC.